The Role of IL-1 Family Members and Kupffer Cells in Liver Regeneration. (22nd March 2016) - Tan, Quanhui; Hu, Jianjun; Yu, Xiaolan; Guan, Wen; Lu, Huili; Yu, Yan; Yu, Yongsheng; Zang, Guoqiang; Tang, Zhenghao
Abstract : Interleukin-1 (IL-1) family and Kupffer cells are linked with liver regeneration, but their precise roles remain unclear. IL-1 family members are pleiotropic factors with a range of biological roles in liver diseases, inducing hepatitis, cirrhosis, and hepatocellular carcinoma, as well as liver regeneration. Kupffer cells are the main source of IL-1 and IL-1 receptor antagonist (IL-1Ra), the key members of IL-1 family. This systemic review highlights a close association of IL-1 family members and Kupffer cells with liver regeneration, although their specific roles are inconclusive. Moreover, IL-1 members are proposed to induce effects on liver regeneration through Kupffer cells.